Enhanced Antitumor Activity by the Combination of Dasatinib and Selinexor in Chronic Myeloid Leukemia - Mariarita Spampinato; Tatiana Zuppelli; Ilaria Dulcamare; Lucia Longhitano; Domenico Sambataro; Annalisa Santisi; Amer M. Alanazi; Ignazio A. Barbagallo; Nunzio Vicario; Rosalba Parenti; Alessandra Romano; Giuseppe Musumeci; et al. (MDPI AG, 2024)
Background: Chronic myeloid leukemia is a hematological malignancy characterized by the abnormal proliferation of leukemic cells. Despite significant progress with tyrosine kinase inhibitors, such as Dasatinib, resistance remains a challenge. The aim of the present study was to investigate the potential of Selinexor, an Exportin-1 inhibitor, to improve TKI effectiveness on CML. Methods: Human CML cell lines (LAMA84 and K562) were treated with Selinexor, Dasatinib, or their combination. Apoptosis, mitochondrial membrane potential, and mitochondrial mass were assessed using flow cytometry. Real-time RT-PCR was used to evaluate the expression of genes related to mitochondrial function. Western blot and confocal microscopy examined PINK and heme oxygenase-1 (HO-1) protein levels. Results: Selinexor induced apoptosis and mitochondrial depolarization in CML cell lines, reducing cell viability. The Dasatinib/Selinexor combination further enhanced cytotoxicity, modified mitochondrial fitness, and downregulated HO-1 nuclear translocation, which has been associated with drug resistance in different models. Conclusions: In conclusion, this study suggests that Dasatinib/Selinexor could be a promising therapeutic strategy for CML, providing new insights for new targeted therapies.